PARENTS' MOTIVATION TO MEMORIZE AL QURAN - Chanifa, Arini Milla; Hendrawijaya, Arief Tukiman (Indonesian Journal of Adult and Community Education, 2025)
This research is motivated by the needs of adults in learning. Adult learning motivation, especially for mothers who memorize the Quran, has various reasons that arise from within and outside themselves when participating in learning activities. One form of activity that attracts attention is the memorization of the Quran which is carried out by mothers at the Raudhatul Quran institution. Raudhatul Quran Institute is a learning institution specifically for learning the Quran for women. The participants who follow this learning are mothers with various work backgrounds. This research aims to describe the mothers' motivation which consists of ibiogenetic motivation, isociogenetic motivation, and itheogenetic motivation. The research method used is a qualitative method using in-depth interviews that focuses on what factors motivate these Quran memorizing mothers in memorizing the Quran at an age that is no longer young. Data was collected through in-depth interviews with mothers who are over 35 years old and are still actively participating in learning to memorize the Quran. The results showed that there were 3 factors that influenced these women in memorizing the Quran, namely biogenetic motives, sociogenetic motives, and theogenetic motives.Keywords: Parents, Motivation, Memorizing the Quran, Factors of Memorizing the Quran